EFFECT OF HUMIC ACID, NUMBER OF CLUSTERS AND CULTIVARS ON GROWTH, FLOWERING AND YIELD OF TOMATO PLANT (Lycopersicon esculantum L.) UNDER PLASTIC HOUSE CONDITIONS - SAIED , ABDUL JEBBAR IHSAN; GULLI, WADULLA GHANIM HAJI (Journal of Duhok University, 2020)
The study was to investigate the effects of two tomato cultivars, Campeon F1 and Calispo F1,two levels of flower clusters ( 6,9 ) clusters.plant-1 and foliar spray of Humic acid at concentrations ( 0 , 15 , 30 and 45 ml.L-1 ) on vegetative growth ,flowers ,yield and yield characteristics of tomato plant grown in plastic house at Duhok governorate, batufa location , guvek village. Results revealed that humic acid at concentration of 30 ml.L-1 significantly increased stem diameter, number of flowers/plant 16.535 mm, 90.42 flowers.plant-1 respectively, and 11.19 flowers/clusters at concentration 45 ml.L-1. So humic acid at concentration of 30ml.L-1 significantly affected the number of fruits.Plant-1, yield per unit area, 82.39 fruits, 23.74 kg/m2. Regarding the effect of level 9 clusters, were obtained the highest value in yield kg.m-2 , yield kg/plant, No. of flower/ plant) while at level 6 cluster in (no. of flower/ cluster). In terms of cultivars, Campeon was overcome by calispo cultivar in fruit fresh weight 75.85, compared with Calispo cultivar 73.30gm.